Corrosion resistance of additively manufactured 316L stainless steel in chloride−thiosulfate environment. (1st December 2020) - Al-Mamun, Nahid Sultan; Haider, Waseem; Shabib, Ishraq
Highlights: Synergistic effects of Cl – and S2 O3 2– on corrosion of 316L stainless steel (SS). Comparative corrosion analysis of additively manufactured (AM) and wrought 316L SS. Significantly improved metastable and stable pitting resistance of AM 316L SS. Better passivation and passive film barrier characteristics of AM 316L SS. Restricted MnS inclusion resulted in superior corrosion resistance of AM 316L SS. Abstract: In this paper, synergistic effects of chloride (Cl – ) and thiosulfate (S2 O3 2– ) on corrosion resistance of additively manufactured (AM) and wrought 316L stainless steel (SS) were investigated in ammonium chloride (NH4 Cl) solution in the absence and presence of different concentrations of sodium thiosulfate (Na2 S2 O3 ). General corrosion induced by Cl – accelerated with the increase of S2 O3 2– concentration for both of the samples. However, pitting resistance of AM 316L SS was found to be at least 4- to 6-fold higher than that of the wrought sample depending on S2 O3 2– concentration. The AM sample demonstrated significantly improved metastable pitting resistance in the presence of S2 O3 2– into Cl – solution. In addition, the passive film of AM 316L SS offered higher charge transfer resistance and film resistance confirming its better stability and barrier characteristics in Cl – –S2 O3 2– environment. The superior corrosion resistance of AM 316 L SS compared to wrought sample was attributed to refined microstructure, absence of MnS micro-inclusions, and lack of Cr depleted regions. Graphical abstract: Image, graphical abstract